Heterotic M2-branes - Neil Lambert (Physics Letters B, 2015)
We construct the action for N M2-branes on S1/Z2. The resulting theory has a gauge anomaly but this can be cancelled if the two fixed point planes each support 8 chiral Fermions in the fundamental of U(N). Taking the low energy limit leads to the worldsheet theory of N free heterotic strings whose quantization induces an E8 spacetime gauge symmetry on each fixed point plane. Thus this paper presents a non-abelian worldvolume analogue of the classic Hořava–Witten analysis.